Síndrome de hiperferritinemia e catarata hereditária: relato de caso - Hortência Teixeira de Morais; Yan Andrade Reis Haddah; Mariza Aparecida Mota; Adriana Aparecida Ferreira; Marta Halfeld Ferrari Alves Lacordia; Sabrine Teixeira Ferraz Grünewald (Sociedade Brasileira de Pediatria, 2023)
INTRODUCTION: The increase in ferritin is a common finding in clinical practice, and may have several causes, such as inflammatory, neoplastic and liver diseases. In addition, ferritin represents the bodys iron stores. The syndrome of hereditary hyperferritinemia and cataract (SHHC) is a rare pathology, which is part of the differential diagnosis of the causes of increased ferritin. The diagnosis of SHHC has a great impact for the patient, as it avoids unnecessary therapeutic interventions, such as bleeding. DESCRIPTION: In the present study, a case of SHHC in a healthy preschooler is reported, in which the finding of elevated ferritin was obtained in an occasional test. The child was submitted to an extensive diagnostic procedure, performed to rule out other causes. DISCUSSION: The prevalence of SHHC is unknown in Brazil, and its variable penetrance can make it difficult to perceive the hereditary character. Thus, this case report and literature review has the importance of alerting about the existence of the pathology, so that pediatricians and other health professionals can make this diagnosis.